Thrombotic Thrombocytopenic Purpura in Dengue Fever - Tze Yuan Tee; Rizna Abdul Cader (Acta Medica Indonesiana)
Thrombotic thrombocytopenic purpura is a rare but life threatening medical condition. Early recognition and treatment of thrombotic thrombocytopenic purpura is important especially in patients who do not present with the classic pentad to reduce the high mortality. Herein, we describe a case of a patient who does not fulfil the classic pentad features thrombotic thrombocytopenic purpura that was induced by dengue fever. The patients’ initial full blood picture did not have all the typical features of microangiopathic haemolytic anaemia but there were fragmented red blood cells. However, even a small number of fragmented red blood cells in the peripheral blood should alert physicians of the possible diagnosis of thrombotic thrombocytopenic purpura together with other symptoms. Furthermore, signs and symptoms of thrombotic thrombocytopenic purpura and dengue fever can overlap such as fever, thrombocytopenia, neurological deficit mimicking dengue encephalopathy and dengue induced acute kidney injury.